2013
DOI: 10.1111/1471-0528.12438
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of anal incontinence during pregnancy and 1 year after delivery: a prospective cohort study

Abstract: Objective To evaluate the prevalence and predictors of anal incontinence (AI) in late pregnancy and 1 year after delivery.Design Prospective population-based cohort study. Setting Two maternity units in Norway 2009-2010.Population Primiparae aged 18 years or over.Methods Primiparae answered questions on the St. Mark's score about AI during the last 4 weeks of pregnancy. One year later, the same questionnaires were distributed by postal mail. Socio-economic and delivery-related data were obtained from hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
58
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 30 publications
9
58
4
Order By: Relevance
“…27,29 Thus the findings in this study may suggest that the complexity of maintaining continence and the embarrassment/ stigma of being unable to control one's bowels may result in AI affecting several QoL domains, and 'Depression' in particular. Based on previous reports that AI during preg- nancy is one of the main predictors of postpartum AI 5,17 , early intervention and information may possibly aid in reducing and preventing postpartum AI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…27,29 Thus the findings in this study may suggest that the complexity of maintaining continence and the embarrassment/ stigma of being unable to control one's bowels may result in AI affecting several QoL domains, and 'Depression' in particular. Based on previous reports that AI during preg- nancy is one of the main predictors of postpartum AI 5,17 , early intervention and information may possibly aid in reducing and preventing postpartum AI.…”
Section: Discussionmentioning
confidence: 99%
“…17 The main reason for choosing primiparous women as our study population was that we wanted a homogeneous study population with no previous deliveries. A pilot study was conducted from May to August 2009, and a cross-sectional study was undertaken between September 2009 and December 2010.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study population consisted of parous Norwegian-speaking women over the age of 18 who reported AI on inclusion (fecal incontinence monthly or more often or St. Mark's score ≥3 points). 10 The study included women with and without obstetrical anal sphincter injury (OASI) and primary sphincter repair. Exclusion criteria were inadequate Norwegian language skills, neurological conditions such as multiple sclerosis and polio, women already receiving PFME treatment before inclusion due to severe postpartum AI or pelvic floor dysfunction, PFM pain/dysfunction, secondary sphincter repair, and being unable to attend treatment and follow up at the nearest available anorectal out-patient clinic or community pelvic floor physiotherapist.…”
Section: Methodsmentioning
confidence: 99%
“…AI was defined as reporting incontinence of stool monthly or more, incontinence of flatus weekly or more, or combinations of two or more incontinence symptoms including fecal urgency on the St. Mark's score. 10,13 Based on the previously documented correlation between the St. Mark's score and patients' subjective improvement following PFME for AI symptoms, a reduction of 2 points or more on the St. Mark's score was considered clinically relevant in this sample of young, healthy women. 11 At Øst-fold Hospital Trust, two-dimensional (2D) and threedimensional EAUS was performed in a side-lying position using a B-K Medical â EAUS machine type 2050 with a 360°probe (B-K Medical Aps, Denmark).…”
Section: Clinical Assessmentsmentioning
confidence: 99%